Occupation and construction processes of the pampas rural area: the case of the Patagones district (Huellas, 2016)
The principal aim of this work is to identify and to describe five historical - territorial moments that determined the spatial organization of the rural areas of the southern pampas in Argentina, and especially the district of  Patagones. To this end, the research strategy used was the case study and temporary cuts, to identify different processes of occupation of the space, in correlation with the explanatory models of the rural world, the historical-territorial moments of the pampas and the territorial national systems. In this way, the events that constructed the rural space of the area under study, located in the south of the province of Buenos Aires, were framed in a space-time process.
Keywords: Occupation processes; pampas rural area; Patagones district